GRAVITY AND MECHANICAL MODELS OF INTERACTION OF CONTINENTAL PLATES IN THE TYAN-SHAN REGION - Burov E.B.; Kogan M.G. (My University, 1990)
There exist several gravity and mechanical models of the continental crust that are useful in the study of the interaction between two lithospheric plates. We shall consider a three-dimensional model of the mechanical interaction between the Asiatic and Indian plates in the Tyan'-Shan'-Tarim-Pamir region. Our method will result in a better agreement between computed and observed gravity anomalies than that achieved by the traditional technique of isostatic admittance. In our technique we shall independently vary the elastic thicknesses of the plates on both sides of the zone of interaction, as well as the boundary conditions and the density distribution in the sediments in the front downwarps.